Intellectual system of students` testing - Sergey V. Barkhudaryan (Изд-во НАН РА)
This paper presents a distance testing system that allows testing of students with dynamically created sequences of tests. The sequence of questions given to students is generated in the process of testing based on his/her answers to the consequent test. Overall performance of developed system is tested by the creation of the corresponding mathematical model.
Keywords: Mathematics; Computer software